Chloride ion permeability of Ultra-high-performance fiber-reinforced concrete under sustained load. (1st May 2023) - Turgeon-Malette, Vicky; Chen, Xuande; Bah, Abdoul Salam; Conciatori, David; Sanchez, Thomas; Teguedy, Mohamed Cheikh; Sorelli, Luca
Abstract: This work aims at investigating the effect of multiple microcracks in Ultra-High Performance Reinforced Concrete (UHPFRC) occurring in service conditions on the apparent chloride diffusion which is critical to guarantee the design lifetime. First, series of preliminary static bending tests were carried out on three UHPFRC beams to characterize their flexural response as well as their microcrack distribution measured by Digital Image Correlation (DIC). Then, a special test set-up was designed to apply and maintain a sustained bending moment on the UHPFRC beams. Finally, some accelerated migration tests were carried out on the micro-cracked UHPFRC beams under sustained bending load. The results showed different chloride penetration rates and profiles in tested UHPFRC beams under different loading levels, and the influence of the microcrack's width on the apparent chloride diffusion coefficient of the considered UHPFRC was clearly identified, which is a precious information for better predicting the service lifetime of a UHPFRC structure. Highlights: An innovative bending-migration test on chloride penetration. Digital Image Correlation analysis method. Numerical modeling of chloride diffusion in cracks.